2020
DOI: 10.1101/2020.05.18.101469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lists with and without syntax: A new approach to measuring the neural processing of syntax

Abstract: 23In the neurobiology of language, a fundamental challenge is deconfounding syntax from semantics. 24Changes in syntactic structure usually correlate with changes in meaning. We approached this 25 challenge from a new angle. We deployed word lists, which are usually the unstructured control in 26 studies of syntax, as both the test and the control stimulus. Three-noun lists (lamps, dolls, guitars) 27 were embedded in sentences (The eccentric man hoarded lamps, dolls, guitars…) and in longer lists 28 (forks,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Regarding the effect’s locus, our results are in line with previous fMRI 9 , 24 , 25 , lesion 49 , and MEG 8 , 21 , 22 findings implicating the LPTL in syntactic processing. However, they contrast with results from two main sets of studies in recent years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the effect’s locus, our results are in line with previous fMRI 9 , 24 , 25 , lesion 49 , and MEG 8 , 21 , 22 findings implicating the LPTL in syntactic processing. However, they contrast with results from two main sets of studies in recent years.…”
Section: Discussionsupporting
confidence: 92%
“…We also note that other MEG studies implicating the LPTL in syntactic processing reported earlier (~ 220 ms) 21 and later (~ 350 ms) 22 clusters; however, they used different designs with lengthier stimuli. Insofar as all LPTL effects tap into the same syntactic computations, this could suggest temporal flexibility in syntactic processing.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Tying in with a growing body of studies on the neurobiological mechanisms underlying syntactic processing (e.g., [26][27][28][29][30]), Uddén et al [31] investigated functional brain activity associated with comprehending sentences varying in LB and RB complexity. They conducted a re-analysis of a functional magnetic resonance imaging dataset from Schoffelen et al [32], where participants (n = 102) read stimulus sentences (n = 360) of varying syntactic complexity.…”
Section: Syntactic Complexitymentioning
confidence: 99%
“…In particular, evidence from neuroimaging and lesion-deficit mapping indicates a role for pMTG in syntactic comprehension and production (Matchin and Hickok, 2020), while pSTS has been implicated via iEEG in hierarchical syntactic computations (Nelson et al, 2017). Posterior temporal regions also provide the strongest and most reliable syntax-specific effects when interpreting lists of nouns embedded within sentences compared to such noun lists in isolation (Law and Pylkkänen, 2021). More broadly, pMTG is robustly associated with basic phrase comprehension deficits across a large number of studies.…”
Section: Minimal Compositionmentioning
confidence: 99%